Changes of the level of high-speed and power abilities of beach handball players of 14-15 years old as a result of the specially selective exercises - Helena Biykova; Yevgeniya Strelnykova; Irina Pomeschikova; Tamara Liakhova (Kharkiv State Academy of Physical Culture, 2015)
Purpose: to determine changes of the level of high-speed and power abilities of beach handball players of 14-15 years old under the influence of the specially selective sets of exercises. Material and Methods: test exercises, one of which is recommended by the training program of CYSS of beach handball, two others were created proceeding from the content of the game activity in beach handball, the analysis of scientific and methodical literature, pedagogical testing, pedagogical experiment, methods of mathematical information processing were used for the definition of the level of development of high-speed and power abilities of beach handball players. Results: the analysis of scientific and methodical literature revealed gaps in questions of training of beach handball players, in particular in physical preparation. It moved us making the use of experience of the educational and training work in beach volleyball, to make sets of exercises, which are aimed at the development high-speed and power abilities of beach handball players. Conclusions: the positive reliable changes are received (t=2,19-2,32 at p≤0,05) of the level of high-speed and power abilities of players of 14-15 years old under the influence of the sets of exercises which are offered by us, allows us to recommend them for use in the educational and training process of beach handball players